Synthesis of N-Methylmorpholinium Derivatives Possessing a 1,3,4-Oxadiazole Core as Feasible Antibacterial Agents against Plant Bacterial Diseases - Xinxin Tuo; Jie Yang; Yedong Zhang; Peiyi Wang (Journal of Chemistry)
To develop a kind of quaternary ammonium compounds that can safely apply in agriculture for managing the plant bacterial diseases, herein, a series of N-methylmorpholinium derivatives possessing a classical 1,3,4-oxadiazole core were prepared and the antibacterial activities both in vitro and in vivo were screened. Bioassay results revealed that compounds 3l and 3i showed the strongest antibacterial activity toward pathogens Xanthomonas oryzae pv. oryzae and X. axonopodis pv. citri with the lowest EC50 values of 1.40 and 0.90 μg/mL, respectively. Phytotoxicity test trials indicated that target compounds bearing a bulky N-methylmorpholinium pendant are safe for plants. The following in vivo bioassays showed that compound 3l could control the rice bacterial blight disease, thereby affording good control efficiencies of 55.95% (curative activity) and 53.09% (protective activity) at the dose of 200 μg/mL. Preliminary antibacterial mechanism studies suggested that target compounds had strong interactions with the cell membrane of bacteria via scanning electron microscopy imaging. Additionally, this kind of framework also displayed certain antifungal activity toward Fusarium oxysporum and Phytophthora cinnamomi. Given the above privileged characteristics, this kind of 1,3,4-oxadiazole-tailored N-methylmorpholinium derivatives could stimulate the design of safe quaternary ammonium bactericides for controlling plant bacterial diseases.